Academic Resilience and Relationship with Meaning of Life Among Koya University Students (Raparin Journal of Humanities (RJH), 2021)
This study aimed to find out the level of academic resilience (AR), meaning of life (MOL) and the relationship between them among students at Koya University. 740 samples were selected randomly. The researcher used two scales; one scale adapted academic resilience scale by Cassidy (2016), and meaning of life scale was developed by the researchers. Principle Component Analysis (PCA) was conducted to test the validity of the meaning of life items. The validity and reliability of the instruments were at convinced level. The result showed that the students have a low level of academic resilience and a high level of meaning of life; the result showed a statistically positive relationship between academic resilience and meaning of life, also the result showed that the academic resilience was predicted meaning of life.